Cementitious Properties and Expansion in Sodium Sulfate Solution of Concrete with Fly Ash and Limestone Powder - วัฒนกุล, ยงยุทธ; กร้ำมาตร, ปิติศานต์; ศิริสวัสดิ์, อิทธิพร; ตั้งเติมสิริกุล, สมนึก (Frontiers in Engineering Innovation Research, 2010)
This research is emphasized on the cementitious properties including normal consistency, setting time of paste, slump and compressive strength of concrete. Moreover, the expansion test of concrete bar exposed to sodium sulfate solution of concrete with fly ash and limestone powder was observed. It was found that the normal consistency of cement paste, cement (type I and V) partially replaced with fly ash, was lower than those of the control mixes. On the other hand" limestone powder replacing cement paste showed equivalent normal consistency to those of the control mixes. Setting time of fly ash cement paste was longer than those of cement only and limestone powder cement pastes. Concrete slump had a tendency to vary inversely with normal consistency of paste. The fly ash concrete exhibited lower strength than limestone concrete and control concrete. Besides, the expansion of concrete sample made with type I cement was larger than that of type V cement and concrete with fly ash and limestone powder. For all ternary binder (cement, fly ash and limestone powder), it was found that the expansion exposed to the sodium sulfate solution of concrete sample with the high CaO fly ash at low replacing content exhibited the large expansion. On the contrary, at the high replacing content of fly ash, the expansion of concrete reduced.